Model of Entrepreneurial Success: A Review and Research Agenda - Yadav, Maheshwar Prasad (Journal of Advanced Academic Research, 2017)
The aim of this paper is to review the entrepreneurial models in order to identify most widespread factors of entrepreneurial success. This study comprises descriptive cum analytical research design. Nine models of entrepreneurial success were reviewed that led to three important findings. The first one is the both micro and macro factors, i.e., individual and environment contexts are necessary to build a comprehensive model of entrepreneurial success. The second is all three types of social, financial and human capital are essential to build a complete model that can explain entrepreneurial success in a better way. The third is the opportunity, environment and resources played the strong role; entrepreneur, innovation, management skills, organization and personal motivation played the moderate role while the weak role-played by the other factors as a whole. Based on the results, the study concludes that the recent research agenda of entrepreneurial success are: Do these factors play vital role for entrepreneurial success in the context of developing country like Nepal? Do entrepreneurs equipped with higher financial capital, social capital, and human capital more likely to be successful? What financial capital, social capital, and human capital matters for entrepreneurial success? How do financial, social, and human resources used by entrepreneurs behave and interact?